(NsOBRANIE SO^INENIJ W PQTI TOMAH(B; s (NrASSKAZY (B/ s (N~ASTX (B3s - (NkUPRIN(B, (Na(B.s ((NmOSKWA(B: s (NpRAWDA(B, s, 1982)
(Nw TRETIJ TOM SOBRANIQ SO^INENIJ a(B. (Ni(B. (NkUPRINA WO[LI RASSKAZY (B1906-1913 (NGODOW TAKIE(B, (NKAK (B"(N{TABS(B-(NKAPITAN rYBNIKOW(B", "(NsULAMIFX(B", "(NgRANATOWYJ BRASLET(B" (NI MNOGIE DRUGIE(B.s
rus
Keywords: (NpOWESTX(B, (NRASSKAZYs